Bibliometric Analysis of Cash Waqf: Publication Trends and Its Impact on Islamic Economic Empowerment - Balqis Syathiri (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
The concept of cash waqf has gained increasing attention in recent years due to its potential to drive economic empowerment within the framework of Islamic finance. As a flexible and scalable form of charity, cash waqf allows for the accumulation and investment of liquid assets, thereby supporting sustainable development initiatives in various sectors, including education, healthcare, and poverty alleviation. Given the growing interest in this area, a bibliometric analysis is essential to assess the trends in research publications related to cash waqf. This study aims to provide a comprehensive overview of the literature, explore the key areas of focus, and examine the impact of cash waqf on economic empowerment in the Islamic world. By analysing the research landscape, the study seeks to identify knowledge gaps and potential future research directions to maximise the role of cash waqf in fostering economic resilience. The bibliometric analysis was performed using the Biblioshiny package from R-Studio, applying quantitative methods and conceptual structure to uncover knowledge discoveries. The screening process on September 11, 2024, identified 135 scholarly contributions related to